In the Foot Step of Consolidating Ummah: Highlights from the 7th Indonesian Muslim Congress - Garadian, Endi Aulia (Studia Islamika, 2020)
Indonesia might be considered as "fortunate". In fact every five years, and often to concur one year after the election took place, Indonesian Muslims have a routine assembly called the Indonesian Muslim Congress (Kongres Umat Islam Indonesia, KUII). The Congress has reached the seventh (KUII VII) in 2020, and one of the its main goals is to consolidate Indonesian Muslims. On top of that, acting as a facilitator, the Indonesian Ulema Council (MUI) through this congress also aspires that Muslims in Indonesia to become the finest community (khayra ummah), to realize the unity of the people (tawhidul ummah), to achieve empowerment of the people (taqwiyatul ummah), to mainstream wasathiyah al-Islam (center and moderate Islam) as well as Islam rahmatan lil alamin, and to install religious values as a spirit of devotion to the nation and state. All of these goals are covered under the grand theme of the congress entitled "Strategies for the Struggle of Indonesian Muslims to Achieve Advanced, Fair and Civilized of Indonesia".